(untitled) (Journal of Environmental Science and Natural Resources, 2015)
The present experiment was conducted to study the culture practice of Thai Koi (Anabas testudineus) with different stocking densities and their growth performance. The study was carried out over a period of 76 days from 22 June, 2008 to 05 September, 2008 in Tarakanda upazila of Mymensingh district. For the study, the experiment was undertaken with 3 treatments (T1, T2 and T3) each having two replications (R1 and R2). Three different stocking densities designed as treatments viz., 550 in T1, 400 in T2 and 350 fry /dec in T3. The fry of same size (length 2.45 cm and weight 5g initially) were stocked and they were fed with commercial pelleted feed according to their body weight. At the very beginning 16% feed were provided with frequency 4 times in a day. It was decrease up to 4.5% before 10 days of harvesting. During the experiment period, water quality was assessed fortnightly. The average temperature was found 28.21±0.870, 28.78±0.510 and 28.76±0.780C in treatments T1, T2 and T3 respectively. The pH ranges were varied between 7.70 to 9.10 among the three treatments. The mean values of dissolve oxygen were 5.33±0.34, 4.23±0.13, 4.16±0.14 mg/L respectively in the three consecutive treatments. The growth performance was determined by measuring length (cm) and weight (g). Treatment-3 where stocking density was less showed the best growth performance followed by T1 and T2. The production was higher 8719.10kg/ha in T1 was obtained from this treatment. DOI: http://dx.doi.org/10.3329/jesnr.v6i2.22116 J. Environ. Sci. & Natural Resources, 6(2): 191-196 2013